THE SIX-PETALLED SOCKET IN THE CIRCLE AS AN INTEGRAL TIME SPATIAL SIGN - Федущак, М. Л. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The hypotheses of scientists regarding the calendar and astronomical function of rock clusters on the mountain Lisina Kosmatska in the Carpathians have been confirmed. The content of the six-petalled socket in the circle commonly used in arts and crafts in the circle as an integral time spatial sign combining directions to the points of solstice and equinox is rococated. An assumption is made about the existence of this mark in the pre-ceramic Neolithic period. The dependence of observation on the line of sight on the features of the relief, the need to use ancient holes and a hump to correct the accuracy of calendar observations is revealed. A guess is made of the knowledge of the righteous riders of the wheel.